Fatigue of Material - A Risk Factor of Design and Exploitation of Technical Systems - Jaromir Maca; Bohus Leitner (Communications - Scientific letters of the University of Zilina, 2002)
Material fatigue of parts of different technical systems belongs to the most frequent causes of boundary states rise and relating operation breakdowns. The paper contains general formulation of reliability of technical systems judging, brief characteristic of basic areas to be taken in account as input into a calculated estimation of technical systems fatigue life and analysis of risk items by its practical application.